Sodium benzoate in locally available soft drinks and its effect on DNA damage and liver function in rats - Mohiuddin, M; Rokeya, Begum; Al Shoeb, Mohammad Abdullah; Kabir, Yearul (Dhaka University Journal of Biological Sciences, 2022)
Sodium benzoate (E211) is used as a preservative in several kinds of food. One of the essential uses of E211 is to preserve non-alcoholic carbonated beverages. The amount of sodium benzoate in 17 local soft drink samples was estimated in the present study. The in vivo effects on biochemical aspects of the liver, kidney function, and DNA damage in lymphocytes were also investigated after oral administration of sodium benzoate in rats over 12 days. The control and experimental groups were fed standard pellet diet and distilled water ad libitum; and administered distilled water (control) and different concentrations (30, 60, and 120 mg/kg body weight) of sodium benzoate once daily through a stomach tube (0.5 ml), respectively. The alkaline comet assay was performed to investigate the possible DNA damage induced by E211 in lymphocytes. At the end of the experiment, after overnight fasting the rats were sacrificed and blood samples were collected. Animals showed no significant weight loss or gain. The investigation revealed that twelve samples contained a higher level, and the rest had trace or below the recommended maximum permitted concentration (150 mg/l) of E211 as a preservative in the soft drinks. The percentage of tail DNA (p < 0.01) and olive tail movement (p < 0.05) was significantly increased in lymphocytes that were treated with high concentration (120 mg/kg body weight) of sodium benzoate, indicated substantially higher DNA damage (3.5 times) in lymphocytes compared to control. Moreover, serum AST activity level was increased significantly (p<0.05) in the group treated with a higher dose (120 mg/kg body weight) of E211, indicating malfunction of the liver. The preservative did not significantly affect serum ALT and ALP activity, total bilirubin, creatinine, and urea level. Nonetheless, our findings suggest that caution should be adopted for using sodium benzoate as a preservative in various food products. Dhaka Univ. J. Biol. Sci. 30(3 CSI): 371-383, 2022 (June)